The Technology and Economy of Care: Gift and Entropy in Gen Urobuchi's Science Fiction. Issue 3 (1st December 2021) - Chu, Leo
Abstract : This paper studies the idea of care in the science fiction of Japanese writer Gen Urobuchi: The Song of Saya (2003), Puella Magi Madoka Magica (2011), and its sequel Rebellion (2013). Utilizing Jacques Derrida's notion of the gift, Bernard Stiegler's critique of entropy, and Takeo Doi's analysis of amae, I examine how these works situate care in relation to thermodynamic and libidinal economy. I demonstrate that care is always an embodied act intertwined with technology and economy, and that by reading care as a pharmakon that both heals and poisons, a "neganthropic" hope can emerge from the entropic system of the Anthropocene.